Probing the Structural Order of Half-Heusler Phases in Sb-Doped (Ti,Zr,Hf)NiSn Thermoelectrics - Fani Pinakidou; Andreas Delimitis; Maria Katsikini (Nanomaterials, 2025)
The nanostructural features of a mechanically alloyed Sb-doped (Ti0.4Zr0.6)0.7Hf0.3NiSn thermoelectric (TE) Half-Heusler (HH) compound were addressed using Transmission Electron Microscopy (TEM) coupled with Energy Dispersive Spectroscopy measurements and Extended X-ray Absorption Fine Structure (EXAFS) spectroscopy. The EXAFS measurements at the Ni-K, Sn-K, Zr-K, and Hf-L3-edge were implemented in an effort to reveal the influence of Hf and Zr incorporation into the crystal with respect to their previously measured TE properties. The substitution of Ti by Hf and Zr is expected to yield local lattice distortions due to the different atomic sizes of the dopants or/and electronic charge redistribution amongst the cations. However, the material is characterised by a high degree of crystallinity in both the short and long-range order, on average, and the nominal stoichiometry is identified as (Zr0.42Hf0.30Ti0.28)NiSn0.98Sb0.02. The synergistic effect of minimization of extended structural defects or lattice distortions and considerable alloying-induced point defect population contributes to the improved TE properties and leads to the previously reported enhancement of the figure of merit of the mixed HHs.